2018
DOI: 10.4309/jgi.2018.39.12
|View full text |Cite
|
Sign up to set email alerts
|

Financially Focused Self-Concept is Associated with Etiological and Maintenance Factors of Gambling Disorder Among Non-Problem Gamblers

Abstract: We examined associations between financially focused self-concept and known etiological and maintenance factors of problematic gambling in a sample of community-based gamblers (N = 412). Although most participants (95.6%) did not report gambling problems, those high in financial focus were more likely to be impulsive, to be dissatisfied with their financial situation, to believe that they have a poor ability to cope with adversity in their life, and to have erroneous beliefs about gambling. The magnitude of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Although perfectionism has been variably defined and measured (for a review, see Dunkley, Blankstein, Masheb, & Grilo, 2006), we, like others (Howell, Anderson, Egan, & McEvoy, 2020;Smith & Saklofske, 2017;Tabri, Wohl, Wood, & Philander, 2018), have argued and found that perfectionism is best understood as a single factor that reflects a striving for flawlessness coupled with critical selfevaluation and concern for how others evaluate the self. Critically, people with such perfectionism are more vulnerable to various forms of psychopathology and disordered behaviors, including eating, anxiety, mood, and personality disorders as well as suicidal ideation (Egan, Wade, & Shafran, 2011;Flett, Hewitt, & Heisel, 2014;Limburg, Watson, Hagger, & Egan, 2017).…”
Section: Perfectionism Disordered Behaviors and Focused Selfconceptmentioning
confidence: 88%
“…Although perfectionism has been variably defined and measured (for a review, see Dunkley, Blankstein, Masheb, & Grilo, 2006), we, like others (Howell, Anderson, Egan, & McEvoy, 2020;Smith & Saklofske, 2017;Tabri, Wohl, Wood, & Philander, 2018), have argued and found that perfectionism is best understood as a single factor that reflects a striving for flawlessness coupled with critical selfevaluation and concern for how others evaluate the self. Critically, people with such perfectionism are more vulnerable to various forms of psychopathology and disordered behaviors, including eating, anxiety, mood, and personality disorders as well as suicidal ideation (Egan, Wade, & Shafran, 2011;Flett, Hewitt, & Heisel, 2014;Limburg, Watson, Hagger, & Egan, 2017).…”
Section: Perfectionism Disordered Behaviors and Focused Selfconceptmentioning
confidence: 88%
“…Measurement invariance, stability, and concurrent validity Some individuals overvalue the importance of their financial success for self-definition and self-worth (Tabri, Wohl, Eddy, & Thomas, 2017). A growing body of research indicates having a financially focused self-concept has predictive utility to identify players at risk of developing gambling problems (Tabri, Hollingshead, & Wohl, 2019;Tabri, Salmon, & Wohl, in press;Tabri, Shead, & Wohl, 2017;Tabri, Werner, Milyavkaya, & Wohl, 2018;Tabri, Wohl, Wood, & Philander, 2018;Tabri, Wood, Philander, & Wohl, in press;Wood, Wohl, Tabri, & Philander, 2017). For example, among community players, showed that greater financial focus was uniquely and moderately associated with disordered gambling severity above and beyond known risk factors for gambling, including personal income, Big-Five personality domains, global self-esteem, personal relative deprivation and materialism.…”
Section: Financially Focused Self-conceptmentioning
confidence: 99%